Entre o barro e o concreto: abandono e resgate de técnicas construtivas na região da Serra do Cipó - Iara Pezzuti dos Santos (2023)
The object of this master thesis is the current production of architecture using vernacular construction techniques and materials – particularly clay – in the Serra do Cipó region. This production is analysed through its construction sites, its socio-spatial context and its products. The research presented was con-ducted by means of fieldwork, direct and participant observation, as well as exploratory and in-depth in-terviews with local builders. The first part of the text presents the conceptual, historical and geographical framework of the study and its procedures, and then discusses the gradual replacement of vernacular ways of building by a production with conventional materials – particularly concrete – and the social impact of these changes. The second part discusses the opposite movement, i.e. the revival of vernacular knowledge and know-how under contemporary conditions, crossed by exogenous knowledge and relations of produc-tion and circulation. This includes drafting a builder typology, that is, a set of ideal types based on concrete cases. Finally, with the aim of supporting technical aid practices and public policies, measures are outlined that expand the possibilities for clay and other local materials to continue to be part of the building culture, attuned to the specificities of each context, with proper symbolic valuation and gradual technical impro-vement, fostering the autonomy of its local agents.